2009
DOI: 10.1097/fbp.0b013e3283305e8d
|View full text |Cite
|
Sign up to set email alerts
|

Performance and subjective effects of diazepam and d-amphetamine in high and low sensation seekers

Abstract: Although sensation-seeking status is associated with age of initiation and amount of drug use among adolescents, and sensitivity to the behavioral and reinforcing effects of drugs among young adults, it is unclear whether sensation-seeking status among adolescents is predictive of sensitivity to the pharmacological effects of drugs (i.e. abuse potential) as adults. This study examined the acute behavioral effects of oral diazepam and d-amphetamine in young adults, ages 18–21 years, who had consistently scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 53 publications
6
23
0
Order By: Relevance
“…Consistent with our previous clinical laboratory studies (i.e., Kelly et al, 2006, 2009; Stoops et al, 2007), the results of the current study demonstrate that individual differences in ZKPQ impulsive sensation-seeking scores are associated with increased sensitivity to the reinforcing effects (i.e., capsules earned on a progressive ratio task) and subjective (i.e., ‘Good Effect’) effects of d-amphetamine. These data extend the results of previous studies by demonstrating that this association is most closely associated with the SS dimension of the impulsive sensation-seeking scale and not related to the Imp dimension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our previous clinical laboratory studies (i.e., Kelly et al, 2006, 2009; Stoops et al, 2007), the results of the current study demonstrate that individual differences in ZKPQ impulsive sensation-seeking scores are associated with increased sensitivity to the reinforcing effects (i.e., capsules earned on a progressive ratio task) and subjective (i.e., ‘Good Effect’) effects of d-amphetamine. These data extend the results of previous studies by demonstrating that this association is most closely associated with the SS dimension of the impulsive sensation-seeking scale and not related to the Imp dimension.…”
Section: Discussionsupporting
confidence: 91%
“…Based on previous research (e.g. Fillmore et al 2009; Kelly et al 2006, 2009; Stoops et al 2007) indicating that the overall ImpSS subscale of the ZKPQ is positively correlated with drug taking behavior and subjective effects, it was hypothesized that SS or Imp would be positively associated with drug taking behavior and subjective drug effects.…”
Section: Introductionmentioning
confidence: 99%
“…The present findings add to a growing body of human behavioral pharmacology research that suggests individuals differ in their sensitivity to acute drug effects based on psychiatric disorder, personality dimensions (e.g., sensation seeking, impulsivity, and risk taking), age, genotype, and gender (Helmus et al, 2005; Hutchison et al, 1999; Kelly et al, 2006, 2009; Kreek et al, 2005; Laviola et al, 1999; Lott et al, 2005; Stoops et al, 2007a; Vansickel et al, 2010). Variations in the above factors have been implicated in increased vulnerability to drug use, abuse, addiction, and relapse.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, experimental assessment of the abuse potential of diazepam has demonstrated that individual differences such as sensation seeking status and alcohol use history can increase the likelihood that diazepam will produce “positive” subject-rated effects or be self-administered in the laboratory (de Wit et al, 1986; Kelly et al, 2009). Similarly, cannabis use history has been associated with a greater propensity to diazepam self-administration (Chutuape and de Wit, 1994), so it might have been predicted that diazepam would have produced robust positive subject-rated effects in the present study.…”
Section: Discussionmentioning
confidence: 99%